2020
DOI: 10.3390/educsci10100275
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Perception of the Usefulness of the Flipped Classroom Methodology

Abstract: In a digital and interconnected context, where educational processes are in constant change, active methodologies take on a relevant role by making students the protagonists of their learning. Among the different possibilities, the flipped classroom stands out for its time optimization, the incorporation of technological resources, and the personalization of the processes. The aim of this research is to analyze the perception of higher education students about the usefulness of the flipped classroom as a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 97 publications
4
32
2
13
Order By: Relevance
“…Other research studies also confirm the distinctive rise of flipped learning, whereby students access information and have more opportunities to interact with each other, due to the wide range of possibilities for sharing opinions and ideas offered by these virtual scenarios. In particular, Colomo-Magaña et al (2020) surveyed 123 trainee teachers who had been learning under the flipped-top classroom model during the 19/20 academic year. They concluded that the application of this flexible methodology promoted the development of oral skills and the improvement of learning abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Other research studies also confirm the distinctive rise of flipped learning, whereby students access information and have more opportunities to interact with each other, due to the wide range of possibilities for sharing opinions and ideas offered by these virtual scenarios. In particular, Colomo-Magaña et al (2020) surveyed 123 trainee teachers who had been learning under the flipped-top classroom model during the 19/20 academic year. They concluded that the application of this flexible methodology promoted the development of oral skills and the improvement of learning abilities.…”
Section: Introductionmentioning
confidence: 99%
“…This learning of competences for a sustainable digital society-digitainability-implies new pedagogical dynamics and methodologies, both in the face-to-face context of the learning and teaching process and in the distance learning modality [19,27,42,[147][148][149], in its variants of blended learning, flipped classroom, inquiry-participatory and smart teaching [6,24,148,[150][151][152][153][154][155]. These variants have, in their differences, the common element of fostering the dynamics of learning through (controlled) learner autonomy, with greater personalization in fostering students' self-learning [ These pedagogical dynamics, which confront an overly transmissive school culture, happen and will happen increasingly through the digital and must be, simultaneously, framed by the digital and the framers of that same digital [20,25,44,48,49,[103][104][105][106][107]150,[162][163][164].…”
Section: Digitainabilitymentioning
confidence: 99%
“…These digitainability learning processes take place in a context of social, economic and even cultural transformations caused by the COVID-19 pandemic [25,105,139,147,[151][152][153]165,166]. Regarding the changes that COVID-19 has caused in education and, specifically, in the learning and teaching process, the author of [167] (p. ix) states that the pandemic has caused "[ .…”
Section: Digitainabilitymentioning
confidence: 99%
“…On the other hand, the use of FL, a methodology centered on constructive and social learning theory, has been proposed. It has been oriented to make the student the protagonist of his or her learning [26].…”
Section: Related Workmentioning
confidence: 99%